Predictors of Mental Health and Job Burnout of Secondary School Teachers in Owerri Education Zone I, Imo State Nigeria - Ugo Philomena N.N PhD; Agu Juliet Ifunanya (Research and Advances in Education, 2024)
Aim of the Study: The study examined the predictor of mental health and job burnout of secondary school teachers in Owerri Education Zone I, Imo State Nigeria. Design/Methodology: 312 teachers from six government-owned secondary schools, participated in this cross-sectional survey study. Along with information on demographics, health-related behaviours, and resilience, the survey tools included the anxiety, stress and depression scale and burnout inventory for educators survey via hierarchical multiple regression analyses and descriptive statistics. Findings: Descriptive statistics were used in the study, and the findings indicated that 10.0% of teachers experienced severe anxiety, 7.3% had severe or extremely severe stress, and 4.3% had severe depression. According to the findings of the study on teacher burnout using hierarchical multiple regression analyses, emotional exhaustion was significantly predicted by age, marital status, family economic status, frequency of exercise, drinking, and resilience; depersonalisation was significantly predicted by drinking, and personal accomplishment was significantly predicted by resilience. The results of the hierarchical multiple regression analyses for the mental health of teachers also showed that age, family economic status, resilience, and exercise frequency were significant predictors of depression; gender, marital status, resilience, and sleep were significant predictors of stress; and marital status, family economic status, exercise frequency, smoking, and resilience were significant predictors of anxiety. Practical Implications: In order to help teachers better grasp the benefits of exercise and sleep for their mental health, schools should collaborate with nearby mental health centres to offer programmes that may be attended in person or virtually in enhancing mental well-being and lowering teacher burnout. Originality/value: This study is the first in Imo State, Nigeria to offer a thorough Teacher Wellness Programme in addition to offering a thorough analysis of teachers’ mental health and burnout. This study offers personal and professional development tools that public health professionals and school administrators can use to improve mental health and reduce teacher burnout.